HYDROLOGICAL STUDY AND ANALYSIS FOR PROPOSED SARTIK DAM PART 2: RESERVOIR CHARACTERISTICS, SIMULATION MODEL, AND FLOOD ROUTING CALCULATIONS - MUSTAFA, BASIL YOUNUS (Journal of Duhok University, 2017)
This research is the part 2 of hydrological study and analysis for proposed Sartik dam which located on the Lesser Zab River, the second largest tributary of Tigris River at 18 km northeast of Altun Kopri town, within Erbil governorate of Iraqi Kurdistan Region. In this part water demand from the dam is calculated, the dam power generating facility with an installed capacity amounting to 156 MW with a maximum discharge of 300 m3/sec. The characteristics of the dam reservoir were calculated, from reservoir sedimentation calculation the dead storage level and capacity was determined and was equal to (309 m.a.s.l., and 104,304,031 m3) respectively. The monthly and annual water losses due to evaporation were calculated from daily recorded evaporation using an equation based on area, volume and elevation curve, and the annual losses were equal to (51,132.366 m3), also the normal reservoir water level (NWL) was fixed at 325 m.a.s.l. which gives live storage capacity equal to (384,846,885), and flooded area equal to (34.184 km2). The simulation model of the dam reservoir, prepared from the calculation of water inflow into the reservoir and water demand including evaporation losses. The inflow was taken for different types of water years, dry (deficit) years (1984, and 1999), average water years (1981, and 1995) inflow, and maximum (flood) water years (1969 and 1988) inflow. From the curves, it is clear that the reservoir starts full at month April and ends full at month March during one year taking into account that the maximum water storage in the reservoir is (489,150,916)m3 and minimum storage is (104,304,031) m3. The flood routing study was done using the (PMF, 1000, 100, 50, and 25) years return periods inflow hydrographs, and stage and volume curve by fixing the crest level of ogee spillway will at 320 m.a.s.l., choosing the number of gated spans equal to 7, the length of each span equal to 12m, and the initial water level of the reservoir was 325 m.a.s.l. The results of this routing will be used to determine the design parameters of the spillway and to determine the actual need of the emergency spillway.